“They Withdrew All I Was Worth”: Automated Teller Machine Fraud and Victims’ Life Chances in Nigeria (2017)
A major downside of the cashless policy introduced by the Central Bank of Nigeria in 2014 is pervasive automated teller machine (ATM) frauds. While fraudsters gain, the life chances of victims are affected. Previous studies in Nigeria had not investigated the effect of ATM frauds on victims’ life chances. Data were generated through in-depth interviews with victims of ATM fraud. Findings show victims suffered post fraud trauma and often depended on friends, parents and relatives to survive the trauma. The reaction of banks to customers’ victimization was unfavorable and unhelpful in compensating the financial losses of customers. We recommend better internal controls for banks and implementation of mechanisms to govern trust and protect customers from victimization.